In the public interest? Planning in the Peak District National Park. (November 2016) - Maidment, Christopher
The recent history of the public interest is one of misappropriation. Practitioners have been found to value the concept but have struggled to articulate how it guides day-to-day planning practice. It has been used to portray a homogeneous public, furthering the interests of the powerful at the expense of recognising social diversity, and leading to calls for the concept's abandonment. Yet this article starts from the argument that the public interest remains the justification that fundamentally underpins planning activities, in light of a continuing need to address collective concerns. To this end, the article adopts the typology put forward by Campbell and Marshall, outlining different ways in which the public interest may practically be addressed. Alongside this, Dewey's work is used to understand how the extent of the public may vary, leading to the use of scale as a way of recognising when different conceptualisations of the public interest might be practically drawn upon. Following this approach, the typology is brought together with scale, as a lens for understanding the extent of a public with a common interest, to form a framework for analysing practice. This framework is used to analyse how the interests of different publics are addressed in a case study of the Peak District, a national park in England. From the case, conclusions are drawn around the need to pay greater attention to the extent of different publics with a common interest and, in turn, how the interests of different publics can be reconciled.